2016
DOI: 10.1039/c6cc02020h
|View full text |Cite
|
Sign up to set email alerts
|

Creating a hyperpolarised pseudo singlet state through polarisation transfer from parahydrogen under SABRE

Abstract: SABRE is harnessed to create a hyperpolarised long-lived state in 2-aminothiazole with >90% efficiency and 27 seconds lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…[44] TheS ABRE technique can hyperpolarize such states,a sw as exemplified for the strongly coupled 1 H-pair in 2-aminothiazole [45] in which the singlet state was accessed in 90 %efficiency by r.f. In this context, singlet states are non-magnetic spin isomers of ac oupled spin-1/2 pair, which are immune to external dipolar coupling.I ti st herefore possible to identify other molecules in which two almost identical protons exist in as inglet state.…”
Section: Sabre-derived 1 H-singlet Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] TheS ABRE technique can hyperpolarize such states,a sw as exemplified for the strongly coupled 1 H-pair in 2-aminothiazole [45] in which the singlet state was accessed in 90 %efficiency by r.f. In this context, singlet states are non-magnetic spin isomers of ac oupled spin-1/2 pair, which are immune to external dipolar coupling.I ti st herefore possible to identify other molecules in which two almost identical protons exist in as inglet state.…”
Section: Sabre-derived 1 H-singlet Statesmentioning
confidence: 99%
“…In this context, singlet states are non-magnetic spin isomers of ac oupled spin-1/2 pair, which are immune to external dipolar coupling.I ti st herefore possible to identify other molecules in which two almost identical protons exist in as inglet state. [44] TheS ABRE technique can hyperpolarize such states,a sw as exemplified for the strongly coupled 1 H-pair in 2-aminothiazole [45] in which the singlet state was accessed in 90 %efficiency by r.f. methods and using aspin-lock as pioneered by Levitt.…”
Section: Sabre-derived 1 H-singlet Statesmentioning
confidence: 99%
“…28 These hyperpolarized nuclear spin singlet states of 15 N 2 diazirines display relaxation time constants of above 20 minutes. Similarly, SABRE was used to hyperpolarize long-lived singlet states on 1 H 2 -pairs, 2930 where polarization decay time constants of above 4 min were observed. 31 Such long hyperpolarization lifetime promises biomolecular tracking and imaging of low concentration analytes on significantly extended timescales.…”
mentioning
confidence: 99%
“…demonstrated that long‐lived 15 N magnetization can be created and integrated into the chemically benign SABRE approach . A parallel approach of using SABRE to prepare hyperpolarized LLS in weakly coupled 1 H spin pairs have also been reported but the magnetization lasted under 90 s …”
Section: Methodsmentioning
confidence: 99%